Three new species of Corynoneura Winnertz from Oriental China (Diptera: Chironomidae: Orthocladiinae) - Fu, Yue; Liu, Tian; Fang, Xiangliang; Wang, Qian; Wang, Xinhua (Zootaxa, 2018)
The males of three species of the genus Corynoneura Winnertz (1846) from Oriental China, Corynoneura cooperio sp. n. Fu & Fang, C. sesquipedalis sp. n. Fu & Fang, C. tumula sp. n. Fu & Fang are described, and morphological characters illustrated.